2022
DOI: 10.1039/d2nr05309h
|View full text |Cite
|
Sign up to set email alerts
|

Recharging upconversion: revealing rubrene's replacement

Abstract: One of the major limitations of solid-state perovskite-sensitized photon upconversion to date is that the only annihilator successfully paired with the perovskite sensitizer has been rubrene, raising the question of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…4d), highlights the rapid emergence of the triplet-related excited state absorption (ESA) features for the respective OSCs. 60 Additionally, evidence of SF within both OSCs can be observed under direct excitation under 400 nm (Fig. 4c and d).…”
Section: Mechanistic Insightsmentioning
confidence: 82%
See 4 more Smart Citations
“…4d), highlights the rapid emergence of the triplet-related excited state absorption (ESA) features for the respective OSCs. 60 Additionally, evidence of SF within both OSCs can be observed under direct excitation under 400 nm (Fig. 4c and d).…”
Section: Mechanistic Insightsmentioning
confidence: 82%
“…Intermolecular coupling effects can already be observed in the two annihilators (rubrene and 1-CBPEA) discussed here. In the solid state, intermolecular interactions enable both SF and TTA, 60 and 1-CBPEA exhibits a significantly redshifted absorption feature caused by aggregation, and significantly redshifted emission. Considering that Schmidt and co-workers have demonstrated that excimer formation can be used to reduce the effects of SF, 70 and fabrication methods can tailor crystal arrangements as shown by Wasielewski and co-workers, which directly influence the intermolecular coupling in bis(phenylethynyl)anthracene (BPEA) and result in a change in the rate of SF, 167 these observations indicate that intermolecular couplings can be utilized to engineer the singlet and triplet energy surfaces to facilitate TTA-UC while suppressing unwanted relaxation pathways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations